2019
DOI: 10.1001/jamaoto.2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and Outcomes of Expansion Sphincter Pharyngoplasty to Treat Lateral Pharyngeal Collapse in Patients With Obstructive Sleep Apnea

Abstract: IMPORTANCE The lateral pharyngeal wall is recognized as an important site of upper airway collapse during sleep in patients with obstructive sleep apnea (OSA), and expansion sphincter pharyngoplasty (ESP) may have promising clinical utility in patients with OSA and lateral pharyngeal wall collapse. OBJECTIVES To evaluate the therapeutic outcomes of ESP in conjunction with other surgical procedures and to investigate indications for ESP in patients with OSA. DESIGN, SETTING, AND PARTICIPANTS Cohort study of 63 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In a multicenter study on 75 patients who refused or did not tolerate CPAP and were treated with EPP, they reported 90% improvement according to Sher's criteria (AHI < 50% and < of 20) [7]. In another study, 63 patients treated with EPP reported an improvement of 67% (according to Sher´s criteria) [8].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study on 75 patients who refused or did not tolerate CPAP and were treated with EPP, they reported 90% improvement according to Sher's criteria (AHI < 50% and < of 20) [7]. In another study, 63 patients treated with EPP reported an improvement of 67% (according to Sher´s criteria) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although lateral pharyngoplasty produced better clinical and PSG outcomes in OSA patients than did UPPP, cross-sectional measurements of the pharyngeal airway did not differ between treatments 16 . In addition, many patients experienced significant dysphagia following lateral pharyngoplasty because it is an invasive process that undermines the superior pharyngeal constrictor muscle, and lateral pharyngoplasty exhibited more complications, such as oronasal reflux of liquid and wound dehiscence, than did relocation pharyngoplasty and ESP 14,21 .…”
Section: Discussionmentioning
confidence: 99%
“…ESP thus creates more powerful tension in the lateral pharyngeal wall and reduces the www.nature.com/scientificreports www.nature.com/scientificreports/ bulk of lateral pharyngeal soft tissue by isolating and rotating the PP muscle super-anterolaterally. In a previous study, we found ESP combined with uvuloplasty to be an effective surgical option for lateral pharyngeal collapse in patients with severe OSA with minimal complications 14 . Based on our clinical data, relocation pharyngoplasty also provided a high cure rate for OSA patients with lateral pharyngeal collapse and effectively reduced lateral pharyngeal bulk, resulting in enhanced soft-palate tension or widening of the pharynx without severe complications after surgery.…”
Section: Pre-op [Mean (Sd)] Post-op [Mean (Sd)] Difference [Mean (Sd)mentioning
confidence: 91%
See 1 more Smart Citation
“…DISE could modify surgical treatment options and procedures in 50% of OSA patients, but the available published studies lack evidence on the association between this impact and surgical outcomes [75]. However, patient selection based on site-specific upper airway behavior has been shown to be of value in improving treatment outcomes [76][77][78][79][80][81][82]. More specifically, a complete circular collapse at the level of the palate (Fig.…”
Section: Evaluation and Inter-and Intrarater Variabilitymentioning
confidence: 99%